Technical Risk Assessment of the 20 kV Submarine Cable Network Development on Tunda Island, Banten - Utama, Frendy Satria; Silvianita, Silvianita (Jurnal Locus Penelitian dan Pengabdian, 2026)
The construction of a 20 kV submarine cable network in Tunda Island is a strategic project to enhance the reliability of the electricity supply. This project faces significant technical risks that require structured risk management. This study aims to identify, analyze, and prioritize technical risk mitigation strategies using a combination of Failure Mode and Effects Analysis (FMEA), Fault Tree Analysis (FTA), and the Analytical Hierarchy Process (AHP). The FMEA results identified ten technical failure modes, with the top three risks based on the Risk Priority Number (RPN) being: Cable jointing failure (RPN 345.31 - Extreme category), Repair/logistics delay (RPN 294.00 - High category), and Mechanical damage to the submarine cable (RPN 231.56 - High category). These findings indicate that human technical and operational aspects, particularly the jointing process and logistical readiness, are the main critical points. The FTA analysis of the critical risks (R4, R10, R1) revealed that the root causes of failure are heavily influenced by human and operational factors, such as non-compliance with installation procedures, the use of non-standard splicing materials, and limitations in logistics and complex administrative bureaucracy. Through AHP, the most dominant mitigation criteria were found to be Electrical System Reliability (weight 0.3389) and External Risk Control (weight 0.2777). Based on this weighting, the most effective and globally prioritized mitigation strategy is the Establishment of Anchor Prohibition Zones and Community Socialization (global weight 0.3722), followed by the Installation of Concrete Mattress (global weight 0.3138). This strategy emphasizes the importance of physical protection combined with regulatory and community participation roles. This research provides a significant contribution in the form of a structured and prioritized technical risk mitigation framework, which can serve as a guide for PLN UID Banten to ensure the safe, efficient, and sustainable execution of the project in a complex maritime environment.